Antimalarial and antimicrobial substances from the endophytic fungus Chaetomium globosum BCC71876 - Nantiya Bunbamrung; Chakapong Intaraudom; Aibrohim Dramae; Nattawut Boonyuen; Wilunda Choowong; Pranee Rachtawee; Chitti Thawai; Pattama Pittayakhajonwut (Natural Product Research, 2024)
) showed the strongest anti-TB activity (MIC 3.13 µg/mL).
Keywords: Microbial Natural Products and Biosynthesis; Genomics and Phylogenetic Studies; Alkaloids: synthesis and pharmacology